2020
DOI: 10.1186/s13054-020-2809-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postextubation high-flow nasal cannula therapy on lung recruitment and overdistension in high-risk patient

Abstract: Background: Postextubation high-flow nasal cannula (HFNC) is used as a support therapy in high-risk patients in ICU. This study aimed to determine the effects of HFNC therapy on lung recruitment and overdistension assessed by electrical impedance tomography (EIT). Methods: Twenty-four patients who received HFNC within 24 h after extubation were prospectively enrolled in this study. EIT was used to monitor regional lung ventilation distributions at baseline (conventional oxygen therapy) and three flow rate leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…22 In addition, Zhang et al evaluated post-extubation HFNC patients using electrical impedance tomography and found that their response to HFNC was variable, with varying degrees of recruitment and overdistension. 23 These results indicate that HFNC might be of benefit to selected patients rather than to all patients with safety concerns.…”
Section: Discussionmentioning
confidence: 90%
“…22 In addition, Zhang et al evaluated post-extubation HFNC patients using electrical impedance tomography and found that their response to HFNC was variable, with varying degrees of recruitment and overdistension. 23 These results indicate that HFNC might be of benefit to selected patients rather than to all patients with safety concerns.…”
Section: Discussionmentioning
confidence: 90%
“…Its clinical applications are to quantify lung collapse, tidal recruitment and lung overdistension under mechanical ventilation. It has also been proposed to evaluate the effects of flow variation on lung recruitment and overdistension under HFNC [ 36 , 37 ]. Ventilation assessment is a correlation of global impedance, unless tidal volume is measured by an external reference ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For ventilation support after extubation, it is important to monitor the respiratory rate and potential changes of lung volume, which could be estimated by the changes of lung impedance measured with EIT. A recent study indicated that overdistension may also occur during HFNC [12]. Combining the detection of pendelluft [13], bedside EIT may provide further insight on lung status, which might be helpful to prevent patient self-inflicted lung injury.…”
Section: Discussionmentioning
confidence: 99%